(untitled) (Orfeu, 2017)
In this paper, the concept of ethos is considered as pertaining to the precepts of Ancient Greece. Two works were taken as a starting point for these considerations: The Republic by Plato, and Politics by Aristotle. By comparing these two philosophers, a discussion was made possible which showed their conception of music’s impact on the placement of emotions and on the character of citizens , as well as the philosophers’ changing opinions in relation to the role of music in society. In the context of this discussion, we conclude that a broader comprehension of ethos is central to the understanding of composers’ musical thought from Classical Antiquity, at least up to the Renaissance.